Development of a reverse transcription loop mediated isothermal amplification assay for the detection of Mouse reovirus type 3 in laboratory mice - Taofeng Lu (Nature Portfolio, 2021)
Abstract Mouse reovirus type 3 (Reo-3) infection is a viral disease that is harmful for laboratory mice. No rapid and accurate detection methods are currently available for this infection. In this study, we describe a rapid, simple, closed-tube, one step, reverse transcription-loop-mediated isothermal amplification (RT-LAMP) assay for Reo-3 and compare our assay with indirect enzyme-linked immunosorbent assay (ELISA). Three sets of RT-LAMP primers were designed by sequence analysis of a specific conserved sequence of the Reo-3 S1 gene. Using RS2 primer set, the RT-LAMP assay required 60 min at 65 °C to amplify the S1 gene in one step by using Reo-3 RNA template and had no cross-reactivity with the other related pathogens, such as Sendai virus (SV), pneumonia virus of mice (PVM), mouse hepatitis virus (MHV), Ectromelia virus (Ect), minute virus of mice (MVM), P. pneumotropica, B. bronchiseptica, K. pneumonia and P. aeruginosa. in our LAMP reaction system. The limit of detection (LOD) of our RT-LAMP assay is 4 fg/μL. The established RT-LAMP assay enabled visual detection when fluorescence detection reagents were added, and was demonstrated to be effective and efficient. We tested 30 clinical blood samples and five artificial positive samples from SPF mice, the concordance between the two methods for blood samples was 100% compared with indirect ELISA and RT-PCR. Considering its performance, specificity, sensitivity, and repeatability, the developed RT-LAMP could be a valuable tool to supply a more effective Reo-3 detection method in laboratory animal quality monitoring.